2009
DOI: 10.2214/ajr.08.1398
|View full text |Cite
|
Sign up to set email alerts
|

CT and PET/CT Findings of T-Cell Lymphoma

Abstract: The extranodal features of T-cell lymphoma are not specific and usually cannot be used to differentiate T-cell lymphoma from other aggressive types of lymphoma. Noncutaneous subtypes frequently manifest with visceral involvement. The goal of CT in initial staging is to exclude visceral involvement. Evidence on the utility of PET/CT is promising, showing high diagnostic value in evaluation of occult disease and treatment response, but the role of PET/CT is evolving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…In the present study, a positive interim PET/CT result was found to be significantly correlated with inferior PFS and OS in T/NK-cell lymphomas, confirming the findings of Choi et al but not the findings of Cahu et al and Pro et al (17)(18)(19). Some technical differences studies may explain this discrepancy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, a positive interim PET/CT result was found to be significantly correlated with inferior PFS and OS in T/NK-cell lymphomas, confirming the findings of Choi et al but not the findings of Cahu et al and Pro et al (17)(18)(19). Some technical differences studies may explain this discrepancy.…”
Section: Discussionsupporting
confidence: 88%
“…Second, patients in the study by Cahu et al were recruited from 5 independent institutions with different PET systems and protocols, possibly leading to heterogeneity in the results of PET. In addition, the sample size in our study was larger (n 5 62 vs. n # 35) (17)(18)(19). More important, our study showed a higher PPV of interim PET/CT (77.9% vs. 39%), meaning a high incidence of relapse or progression among patients with positive results at interim PET/CT.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In hepatosplenic TCL, hepatosplenomegaly is seen at CT and is typically the only imaging finding. [4,5] The described case had similar findings on CT.…”
Section: Discussionsupporting
confidence: 66%
“…[4,6] Use of FDG PET/CT in cutaneous and subcutaneous panniculitislike TCL suggests that it outperforms physical examination in evaluation for subcutaneous lesions. In addition, PET/CT can be used to monitor the response to therapy of lymph nodes that are FDG-avid but do not meet the size criteria for staging (< 1 cm).…”
Section: Discussionmentioning
confidence: 99%